La incidencia del crimen organizado y los condicionamientos estructurales en la violencia homicida. El caso de Montevideo (2015-2024). (Delito y Sociedad, 2025)
The accelerated growth of homicidal violence experienced in Uruguay in recent years poses a series of interpretive challenges. In general terms and at a macro level, the country stands out for having low levels of poverty and inequality, a high human development index, a welfare state with a long tradition and the existence of a remarkable institutionality with wide international recognition. Despite the presence of these factors, which are usually postulated as predictors of low levels of violence, since 2019 Montevideo became the second South American capital with the highest homicide rate, giving rise to interpretations of this escalation linked to territorial disputes led by organized crime associated with drug trafficking. To appeal to the impact of a sociologically undefined category due to the breadth and diversity of phenomena it includes does not solve the problem raised, since the country does not meet the conditions that are frequently raised: it is not a producer and its consumer market is not expanding but rather shrinking due to demographic stagnation and aging, in addition to the implementation in 2013 of legislation that regularized the commercialization of cannabis. At the same time, its recognized roles as a financial center friendly to money laundering and porous port borders for large shipments should temper rather than encourage the bloody disputes that, due to their increasing cruelty, alarm the population and attract the attention of international organizations, consequently increasing operational difficulties and transaction costs. The article discusses these arguments and presents the processing of socioeconomic indicators and official statistics on homicides at the level of municipalities and police stations in the capital, locating at the micro level the existence of deep and persistent territorial asymmetries as the setting where homicidal behavior with particular characteristics is deployed.
Keywords: Organized Crime} – Poverty – Inequality – Homicides – Drug Trafficking